Assessing the efficacy of electrocardiogram for heart rate evaluation during newborn resuscitation at birth: a prospective observational study - Kee Hyun Cho; Hyun Su Lee; Eun Sun Kim (Clinical and Experimental Emergency Medicine, 2025)
Objective This study assessed the efficacy of electrocardiogram (ECG) compared to pulse oximetry (PO) in detecting heart rate (HR) during high-risk newborn resuscitation. Methods A prospective observational study was performed with high-risk delivery cases to measure the time required for HR detection. A conventional PO and a standard ECG monitor were used for HR assessment. Results Forty-one infants were analyzed in the study, and 11 needed resuscitation. The study population was divided according to gestational age (GA): 9 were GA <32 weeks, 28 were GA 32–35 weeks, and 4 were GA ≥36 weeks. Time from ECG placement to HR detection (median, 30 seconds; interquartile range [IQR], 20–43.5 seconds) was significantly faster than that from PO placement (median, 125 seconds; IQR, 100–175 seconds; P<0.001). Time from ECG placement to HR detection was shortest in infants with GA <32 weeks at birth (19 seconds [IQR, 11.5–30.0] for GA <32 weeks vs. 34.5 seconds [IQR, 25.0–44.3] for GA 32–35 weeks vs. 39.5 seconds [IQR, 30.0–64.8] for GA ≥36 weeks; P=0.039). Conclusion ECG effectively evaluated HR during neonatal resuscitation compared to PO. Low-GA infants who require resuscitation may benefit from HR evaluation with nearby standard ECG.